The globalisation of angel investments - Josh Lerner; Antoinette Schoar; Stanislav Sokolinski; Karen Wilson (Bruegel, 2015)
The last decade has seen a rapid expansion and deepening of the types of vehicles that fund start-up firms in the U.S. and worldwide. In particular, we have seen a growing role of angel groups and other more "individualistic" funding options for start-ups, such as super angels or crowd sourcing platforms. We seek to understand the nature and consequences of angel investments across a variety of geographies with varying levels of venture capital markets and other forms of risk capital. We ask whether angel investors improve the outcomes and performance of the start-ups they invest in. Furthermore we want to understand whether and how the types of firms that seek angel funding vary with the overall entrepreneurial ecosystem in a country. We examine the records of 13 angel investment groups based in 12 nations and with applicants for financing transactions from 21 nations, examining both the applicants that were considered and rejected and those that were funded. Our key findings from the analysis are two-fold. First, angel investors have a positive impact on the growth of the firms they fund, their performance, and survival. Second, we find that the selection of firms that apply for angel funding is different across countries.
Keywords: 330